2020
DOI: 10.1002/anie.202000406
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Reactivity of Cationic Boron Complexes Distorted by Pyridine‐based Pincer Ligands: Isolation of a Photochemical Hofmann–Martius‐type Intermediate

Abstract: A family of cationic boron complexes was synthesized, using a dianilidopyridine pincer ligand, which imposes in‐plane distortion of the geometry at boron towards T‐shaped. Reactivity of these cations toward hydride and base was investigated, and the utility of these cations as precursors to a variety of π‐conjugated BN heterocycles was demonstrated. 300 nm irradiation of a deprotonated pincer boron complex triggered a C−N cleavage/C−C formation yielding a dearomatized boryl imine, which has a structure akin to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 88 publications
1
4
0
1
Order By: Relevance
“…Trianionic pincer-type ligands are well-known supporting structures within transition-metal organometallic chemistry, and their ability to enforce constrained geometries has likewise found applications in main-group chemistry. Within this vein, we have reported the preparation of the phosphorus compound 1 based on the trianionic N , N , N -chelate {N­[ o -NMe-C 6 H 4 ] 2 } 3– , which adopts a nontrigonal local geometry about phosphorus as a function of the ring constraints (Figure , top). , Whereas the reaction of phosphorus­(III) amides with protic pronucleophiles commonly leads to phosphitylation by metathetical exchange, , compound 1 undergoes intermolecular oxidative addition of amine N–H and alcohol O–H bonds to give pentacoordinate σ 5 -P adducts 1 ·[H]­[E] (E = OR, NHR). In situ spectroscopy demonstrated that the observed oxidative addition reactions proceed via a stepwise mechanism involving initial E–H bond cleavage by phosphorus-ligand cooperation, followed by subsequent intramolecular σ 3 -P → σ 5 -P tautomerism (Figure , top).…”
Section: Introductionsupporting
confidence: 82%
“…Trianionic pincer-type ligands are well-known supporting structures within transition-metal organometallic chemistry, and their ability to enforce constrained geometries has likewise found applications in main-group chemistry. Within this vein, we have reported the preparation of the phosphorus compound 1 based on the trianionic N , N , N -chelate {N­[ o -NMe-C 6 H 4 ] 2 } 3– , which adopts a nontrigonal local geometry about phosphorus as a function of the ring constraints (Figure , top). , Whereas the reaction of phosphorus­(III) amides with protic pronucleophiles commonly leads to phosphitylation by metathetical exchange, , compound 1 undergoes intermolecular oxidative addition of amine N–H and alcohol O–H bonds to give pentacoordinate σ 5 -P adducts 1 ·[H]­[E] (E = OR, NHR). In situ spectroscopy demonstrated that the observed oxidative addition reactions proceed via a stepwise mechanism involving initial E–H bond cleavage by phosphorus-ligand cooperation, followed by subsequent intramolecular σ 3 -P → σ 5 -P tautomerism (Figure , top).…”
Section: Introductionsupporting
confidence: 82%
“…[50b] Recently, Milstein and co-workers have reported a family of geometrically distorted three coordinated boron cations (37 a-c; Scheme 40) using a dianilidopyridine pincer ligand (L 12 ), which shows in-plane distortion toward a Tshaped geometry. [53] Treatment of 37 a-c with two equivalents of a base (LiN(SiMe 3 ) 2 ) generated the neutral BN 3 compounds (38 a-c, Scheme 40). Single crystal x-ray diffraction study reveals that the N2À BÀ N3 bond angles in 37 a and 38 a are 151.9°and 151.8°respectively, compared to 145.7(3)°in 36 a.…”
Section: Geometry Constrained Group 13 Compoundsmentioning
confidence: 99%
“…Martin and co‐workers utilized the sterically rigid triamide ligand system ( L 2 ) for the isolation of geometry constrained boron‐containing complexes ( 36 a – c ), which resulted in perturbed bond angles (N2−B−N3 of 36 a =145.7(3)° (Scheme ) . Recently, Milstein and co‐workers have reported a family of geometrically distorted three coordinated boron cations ( 37 a – c ; Scheme ) using a dianilidopyridine pincer ligand ( L 12 ), which shows in‐plane distortion toward a T‐shaped geometry . Treatment of 37 a – c with two equivalents of a base (LiN(SiMe 3 ) 2 ) generated the neutral BN 3 compounds ( 38 a – c , Scheme ).…”
Section: Geometry Constrained Group 13 Compoundsmentioning
confidence: 99%
“…Milstein, who was last featured in detail when he was elected to the US National Academy of Sciences, has also received the 2020 Gabor A. Somorjai Award for Creative Research in Catalysis by the American Chemical Society. In a Communication in Angewandte Chemie , Milstein and co‐workers recently described distorted cationic boron complexes with pyridine‐based pincer ligands …”
Section: Awarded …mentioning
confidence: 99%